The nutrition transition in Ecuador: an ethnographic approach to diet and diabetes. - Dirocco, Anne Marie (2013)
Modernization and urbanization have led to startling changes in dietary and lifestyle habits across the globe. One interpretation of this process of changing food habits is called the nutrition transition, which describes how modern diets high in sugars, salts, fats and processed foods are leading to unprecedented rates of non-communicable diseases like overweight, obesity, diabetes and heart disease; the nutrition transition also has serious implications for the environment. The nutrition transition in Ecuador is a pertinent dilemma considering that over the past ten years, non-communicable diseases have been top killers in the country. While attempts to address the issue in Ecuador have been disproportionately quantitative in design, this investigation presents an ethnographic approach, taking into careful consideration urban-rural dynamics, socioeconomic factors, generation, and gender. Interviews and observations were carried out in one rural family and one urban family who have members suffering from diabetes, a non-communicable disease. Additionally, current programs and policies that are responding to the nutrition transition in Ecuador are reviewed.